EFFECT OF INITIAL SOLVENT SLURRY INSIDE THE REACTOR FOR FISCHER-TROPSCH SYNTHESIS - Ne’matov , Khusan; Abdullaev , Bakhtishod; Sayfullaev , Temurbek (Sanoatda raqamli texnologiyalar, 2024)
The effect of starting solvent on the performance of cobalt-based catalysts and potassium precipitated iron catalysts was investigated during Fischer-Tropsch (FT) synthesis using a continuously stirred tank reactor. In this study, starting solvents of four different molecular weights were tested: Polywax-3000 (MW (average molecular weight) = 3000), Polywax-2000 (MW = 2000), Polywax-500 ( MW = 500) and C-30 oil (MW = 420). Conversion and selectivity (methane, C5?, and CO2) were similar for all starting solvents tested for potassium-supplied precipitated iron catalysts, with significant differences in starting solvent for the iron catalyst tested. there is. indicates no effect. However, with the cobalt catalyst, the conversion varied with the solvent, with the conversion increasing as the molecular weight of the solvent decreased. This is believed to be due to the particle size of cobalt alumina catalysts compared to the iron used. Under synthesis conditions, the iron catalyst produces a measurable fraction of 1-3 micron size particles in the lower range of the particle size distribution, while the alumina support maintains the same, larger size during synthesis. Thus, the decrease in conversion with time may be the result of solvent filling of the pores in the interior of the catalyst, which increases with increasing molecular weight of the starting solvent. Wax formation must be considered when deriving conversion and aging data for FT catalysts.